2020
DOI: 10.21107/agriekonomika.v9i2.8754
|View full text |Cite
|
Sign up to set email alerts
|

Social Economy and Digital Mapping of Subak Sembung Ecotourism

Abstract: The social, cultural, economic, and environmental potentials in Subak Sembung are not well-developed, such that these potentials have not been adequately explored by the local community. This study aimed to describe the synergy between subak and the ecotourism in supporting the sustainable national food stability program. Subak Sembung selected as the study location because its location in the middle of Denpasar City and already developed as ecotourism sites. There were 66 participants involved in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To deal with these challenges, it is encouraged to adopt technology that promotes fast exchange of information between farmers, stakeholders, and the public. The needed information, e.g., farming activities and existing facilities on rice fields, can be obtained and presented using mapping technologies [37,38].…”
Section: Technological Dimensionmentioning
confidence: 99%
“…To deal with these challenges, it is encouraged to adopt technology that promotes fast exchange of information between farmers, stakeholders, and the public. The needed information, e.g., farming activities and existing facilities on rice fields, can be obtained and presented using mapping technologies [37,38].…”
Section: Technological Dimensionmentioning
confidence: 99%
“…Denpasar City had 12,778 Ha of land that composed of 2,409 Ha (18,85%) of rice paddy field and 510 Ha (3,99%) of non-agricultural land. Studied by Pradnyadewi et al, (2021), Arisena et al, (2020), and Darmawan et al, (2021) identified an urban farming in Denpasar City, namely Subak Sembung. Utilizing the 104 Ha of land areas, Subak Sembung consistently shows vibrant agricultural activities amid Denpasar City.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the environmental services provided by the Subak rice fields to protect soil fertility from erosion has not been widely studied in Bali. The previous research placed more emphasis on studying soil fertility, mapping and the socio-demographics conditions of Subak [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%